Commentary on the Old Testament ; v. 7 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890 (Peabody, MA Hendrickson, 1996)
Contents : v. 7 : Isaiah / F. Delitsch. Includes bibliographical references.
Reprint of the T & T Clark, 1866-91 English ed.
Keywords: Bible. O.T. -- commentaries